2022
DOI: 10.1021/jacs.1c12421
|View full text |Cite
|
Sign up to set email alerts
|

Modulating Chemical Environments of Metal–Organic Framework-Supported Molybdenum(VI) Catalysts for Insights into the Structure–Activity Relationship in Cyclohexene Epoxidation

Abstract: Solid supports are crucial in heterogeneous catalysis due to their profound effects on catalytic activity and selectivity. However, elucidating the specific effects arising from such supports remains challenging. We selected a series of metal− organic frameworks (MOFs) with 8-connected Zr 6 nodes as supports to deposit molybdenum(VI) onto to study the effects of pore environment and topology on the resulting Mo-supported catalysts. As characterized by X-ray absorption spectroscopy (XAS) and single-crystal X-ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 48 publications
2
27
0
Order By: Relevance
“…Metal–organic frameworks (MOFs), derived from different metal-oxo nodes and organic linkers with persistent porosity, large specific surface areas, and uniform open cavities, are distinct crystalline porous materials. Due to the noticeable thermal and chemical durability and the availability of abundant and spatially distributed binding sites, MOFs containing various metal-oxo nodes and carboxyl organic linkers are one of the most widely studied categories. So far, to obtain a better activity in diversified fields, a variety of strategies have been used for MOFs, including adding acid modulators, , changing solvents, loading metals, constructing heterojunctions, and so forth. In this context, this might be applicable in redox reactions powered by light over MOFs.…”
Section: Introductionmentioning
confidence: 99%
“…Metal–organic frameworks (MOFs), derived from different metal-oxo nodes and organic linkers with persistent porosity, large specific surface areas, and uniform open cavities, are distinct crystalline porous materials. Due to the noticeable thermal and chemical durability and the availability of abundant and spatially distributed binding sites, MOFs containing various metal-oxo nodes and carboxyl organic linkers are one of the most widely studied categories. So far, to obtain a better activity in diversified fields, a variety of strategies have been used for MOFs, including adding acid modulators, , changing solvents, loading metals, constructing heterojunctions, and so forth. In this context, this might be applicable in redox reactions powered by light over MOFs.…”
Section: Introductionmentioning
confidence: 99%
“…A detailed understanding of the reaction mechanisms involved in gas-phase catalysis at the well-defined MOF metal nodes would provide critical insight into how these uniquely tunable materials can be used for rational catalyst design. There have been many studies of catalysis at MOF nodes in the liquid phase for a variety of reactions , such as hydrogenation, oxidation, , epoxidation, , cycloaddition, hydrolysis of phosphonate esters, , and cyanosilylation of aldehydes. , Investigation of MOFs as gas-phase catalysts is a more recent development despite the economic advantages arising from the ease of separation in gas phase reactions . Studies by Farha, Hupp, and co-workers have shown that Ni species deposited on the Zr-based nodes of NU-1000 are active for ethylene hydrogenation. Similarly, Gates and co-workers demonstrated that Rh and Ir ions anchored to Zr 6 nodes of UiO-67 are catalysts for gas-phase hydrogenation and isomerization of ethylene. , Reports of sustained gas phase catalysis occurring directly at the metal ions that compromise the MOF nodes are relatively rare; these reactions have involved the dimerization and oligomerization of ethylene at the paddlewheel nodes of Ru 3/2+ -HKUST-1 analogs and the Ni 2+ paddlewheel nodes of Ni-MOF-74, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…A detailed understanding of the reaction mechanisms involved in gas-phase catalysis at the well-defined MOF metal nodes would provide critical insight into how these uniquely tunable materials can be used for rational catalyst design. There have been many studies of catalysis at MOF nodes in the liquid phase for a variety of reactions 2,16−18 such as hydrogenation, 19 oxidation, 20,21 epoxidation, 22,23 cycloaddition, 24 hydrolysis of phosphonate esters, 25,26 and cyanosilylation of aldehydes. 27,28 Investigation of MOFs as gas-phase catalysts is a more recent development despite the economic advantages arising from the ease of separation in gas phase reactions.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Among the thousands of reported metal‐organic frameworks (MOFs), [ 1‐11 ] Zr‐based MOFs have been widely investigated in the past several years, [ 12‐17 ] in part due to their robust frameworks with unique topologies, chemical and hydrothermal stabilities. Among them, this subclass of Zr‐MOFs built from hexanuclear Zr‐oxocarboxylate clusters has attracted great attention of chemists and materials scientists, [ 18‐27 ] such as now commercially available as UiO‐66.…”
Section: Background and Originality Contentmentioning
confidence: 99%